DIPLOMASI EKONOMI INDONESIA DALAM MENYIKAPI DELISTING PRODUKRUMPUT LAUT INDONESIA OLEH US NATIONAL ORGANIC STANDARD BOARD (NOSB) - Ketty Rummeinur Kusuma (2020)
With Indonesia being the largest archipelagic country in the world, it can be obtained as a maritime economy. Indonesia has good prospects in the maritime economy because all of the largest economic activities are derived from marine resources, specifically seaweed. The seaweed trade in the global market is about very good value for Indonesia. The United States is Indonesia's main export destination for seaweed, but opposes the emergence of the United States, which is representing a petition related to seaweed and also the community that makes the United States government must remove or remove Indonesian seaweed from the list of organic food ingredients, by involving this issue. attracts most relevant institutions and governments. This research is intended to analyze how the efforts and strategies of Indonesia's economic diplomacy in addressing the delisting of Indonesian seaweed products by NOSB. The method applied and used by researchers is a descriptive qualitative method that explains more deeply the efforts associated with delisting by the NOSB. This study uses diplomacy theory to analyze Indonesian diplomacy in overcoming the delisting problem. and in this study the concept of economic diplomacy is used to analyze Indonesia's strategy in dealing with delisting conducted by NOSB From this research based on economic diplomacy theory and non-tariff barriers, the Indonesian government finally succeeded in returning Indonesian seaweed products tovii the United States market and was able to establish cooperation with the United States, and make the United States government remove the delisting policy.